Participación juvenil en diseño, investigación y creación: tres estudios de caso sobre proyectos de co-diseño con adolescentes - Lombana-Bermúdez, Andres (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2023)
Co-design or participatory design with young people is na innovative methodological approach that has been and is being Applied in various sectors to develop research and creative processes. From interventions in the area of health to curriculum design projects in schools, to research on media literacy, the inclusion and participation of young people in this type of initiatives offers multiple possibilities for the generation of knowledge, products, and services. In this article I present ana anlyzis of three co-design projects with young people aged 12-18, developed in schools and youth organizations in Austin (2012), Boston (2016-17), and Bogotá (2019). Drawing on cualitative data and using the case study methodology, I inquire about the challenges and opportunities that emerge with this type of interventions and the different forms of participation that can be configured when researching and creating with adolescents. Regarding the opportunities, the article focuses on the potential of using youth digital cultures and practices to investigate and solve problems situated in local contexts, and to design educational resources and learning experiences in a collaborative and participatory way. In terms of challenges, the article highlights the logistical and methodological challenges, and the ethical considerations of co-design process with youth.